Stereotactic Irradiation of GH-Secreting Pituitary Adenomas - G. Minniti; C. Scaringi; D. Amelio; R. Maurizi Enrici (International Journal of Endocrinology)
Radiotherapy (RT) is often employed in patients with acromegaly refractory to medical and/or surgical interventions in order to prevent tumour regrowth and normalize elevated GH and IGF-I levels. It achieves tumour control and hormone normalization up to 90% and 70% of patients at 10–15 years. Despite the excellent tumour control, conventional RT is associated with a potential risk of developing late toxicity, especially hypopituitarism, and its role in the management of patients with GH-secreting pituitary adenomas remains a matter of debate. Stereotactic techniques have been developed with the aim to deliver more localized irradiation and minimize the long-term consequences of treatment, while improving its efficacy. Stereotactic irradiation can be given in a single dose as stereotactic radiosurgery (SRS) or in multiple doses as fractionated stereotactic radiotherapy (FSRT). We have reviewed the recent published literature on stereotactic techniques for GH-secreting pituitary tumors with the aim to define the efficacy and potential adverse effects of each of these techniques.